2013
DOI: 10.1037/a0034694
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effect of defensive denial on relationship instability.

Abstract: Maladaptive communication may often undermine the long-term stability of romantic relationships. We hypothesized that defensive denial may be a salient type of maladaptive communication that erodes relationship stability over time because it may lead to more caustic conflict-escalating behaviors. Additionally, we hypothesized that defensive denial observed in romantic relationships could be linked back to defensive denial observed in the family of origin. Using data from the Family Transitions Project, we spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The final four items were: "I have thought that my relationship might be in trouble," "The thought of breaking up or ending the relationship has crossed my mind," "I have discussed ending my relationship with a close friend," and "My partner or I have seriously suggested the idea of ending our relationship." Similar revisions of this measure used with unmarried different-sex cohabitors have demonstrated good psychometric properties (Lannin, Bittner, & Lorenz, 2013). Participants responded to each item on a 5-point scale (0 ϭ never; 4 ϭ very often).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final four items were: "I have thought that my relationship might be in trouble," "The thought of breaking up or ending the relationship has crossed my mind," "I have discussed ending my relationship with a close friend," and "My partner or I have seriously suggested the idea of ending our relationship." Similar revisions of this measure used with unmarried different-sex cohabitors have demonstrated good psychometric properties (Lannin, Bittner, & Lorenz, 2013). Participants responded to each item on a 5-point scale (0 ϭ never; 4 ϭ very often).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we replaced the word “marriage” with “relationship” and “divorce” with “breaking up or ending my relationship” and deleted one item that asked about consulting an attorney regarding a possible divorce or separation, given that many same-sex couples do not have legal recognition. The final four items were: “I have thought that my relationship might be in trouble,” “The thought of breaking up or ending the relationship has crossed my mind,” “I have discussed ending my relationship with a close friend,” and “My partner or I have seriously suggested the idea of ending our relationship.” Similar revisions of this measure used with unmarried different-sex cohabitors have demonstrated good psychometric properties (Lannin, Bittner, & Lorenz, 2013). Participants responded to each item on a 5-point scale (0 = never ; 4 = very often ).…”
Section: Methodsmentioning
confidence: 99%
“…Salas, Garcia-Martin, Fuentes, Bernedo (2015) found that foster children's self-esteem was negatively affected by criticism and rejection. Lannin, Bittner, and Lorenz (2013) noted that a defensive approach to communicating in conflict often increased conflict. In addition to an increase in behavioral problems, an increase in conflict between foster children and foster parents was associated with poor bonding experiences among foster children (Denuwelaere & Bracke, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The final 4 items were: (“I have thought that my relationship might be in trouble,” “The thought of breaking up or ending the relationship has crossed my mind,” “I have discussed ending my relationship with a close friend,” and “My partner or I have seriously suggested the idea of ending our relationship”). Similar revisions of this measure used with unmarried different-sex cohabiting couples have demonstrated good psychometric properties (Lannin et al, 2013). Participants responded to each item on a 5-point scale (0 = never ; 4 = very often ).…”
Section: Methodsmentioning
confidence: 99%